(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article deals with the study of the moral-philosophical and mythopoetic understanding of a person, age and life in Mikhail Bulgakov’s novel "The Master and Margarita", as well as the concepts of a cultural approach in the poetics of the novel.